Modeling High Mass X-Ray Binaries to Double Neutron Stars through Common Envelope Evolution - Yu-Dong Nie; Yong Shao; Jian-Guo He; Ze-Lin Wei; Xiao-Jie Xu; Xiang-Dong Li (The Astrophysical Journal)
We present detailed evolutionary simulations of wide binary systems with high-mass (8–20 M _⊙ ) donor stars and a 1.4 M _⊙ neutron star. Mass transfer in such binaries is dynamically unstable, and common envelope (CE) evolution is followed. We use a recently developed prescription to deal with CE evolution and consider various CE ejection efficiencies varying in the range of 0.1–3.0. We focus on the evolutionary consequences of the binaries that survived CE evolution. We demonstrate that it is possible for the binaries to enter a CE decoupling phase (CEDP) when the donor stars are partially stripped, leaving a hydrogen envelope of ≲1.0–4.0 M _⊙ after CE evolution. This phase is expected to last ∼10 ^4 –10 ^5 yr, during which mass transfer occurs stably via Roche lobe overflow with super-Eddington rates. Identification of some X-ray binaries in a CEDP is important for the understanding of the physics of CE evolution itself, the origin of ultraluminous X-ray sources, and the recycling process of accreting pulsars. Also, we discuss the formation of double neutron stars and the occurrence of ultrastripped supernovae according to the results from our simulations. On the whole, the properties of post-CE binaries are sensitive to the options of CE ejection efficiencies.